Reformulation of Third-Party Protection in Online Loan Collection Provisions - Ni Putu Yuliana Kemalasari; KMS Herman (International Forum of Researchers and Lecturers, 2025)
The rise of online loans (commonly known as pinjol) reflects the broader transformation of conventional financial systems into digital platforms, influenced heavily by the rapid development of financial technology (fintech). While online loans offer ease and accessibility, their implementation has raised significant legal concerns—particularly relating to the violation of privacy and the rights of third parties who are not directly involved in the loan agreement. One of the main legal issues occurs during the debt collection process, where third parties—often relatives, colleagues, or acquaintances of debtors—are subjected to intimidation, unlawful dissemination of personal data, and public defamation. These practices are not only unethical but also infringe on the privacy and dignity of uninvolved individuals. This article employs a legal research method using a normative approach. As a normative legal study, it analyzes laws, regulations, and legal literature relevant to the problem. The study finds that current legal regulations do not adequately protect third parties from the harmful practices associated with online loan collections. In response, there is a pressing need for regulatory reform. This includes strengthening personal data protection laws, enhancing supervision mechanisms over fintech companies, and ensuring that legal standards are consistently enforced. Reformulating these regulations will help address the legal vacuum and ensure greater legal certainty and protection for all individuals affected by online loan transactions. Through comprehensive policy changes and stronger enforcement, the negative impact of online loans can be mitigated, safeguarding both borrowers and uninvolved third parties.